SEMIOTIC ANALYSIS OF LIBRARY HOMEPAGES: A CASE STUDY OF THE UNIVERSITY OF MANAGEMENT AND TECHNOLOGY (UMT), LAHORE, PAKISTAN - Mariym Muhammad Ismail , Muhammad Waseem Zia, Kamaluddeen Isa El-Kalash (IJoLIS, 2024)
Purpose- Signs and symbols plays an important role in our lives because they help us to convey messages even without written words. With the invention of the internet and the evolution of web technologies, the universe became a global village because the internet facilitated a better and faster avenue for human communication. In libraries and allied information science terrains, the internet fostered the use of Websites, to portray the intellectual contents that are domiciled in them. On the library websites, users can ascertain the timings, collections, policies etc. of a particular library because the icons that are visible on a homepage usually make it very attractive to the user, as well as convey the interpretations of the images without textual inscriptions.